2018
DOI: 10.3847/1538-4357/aabcbd
|View full text |Cite
|
Sign up to set email alerts
|

The MOSDEF Survey: A Stellar Mass–SFR–Metallicity Relation Exists at z ∼ 2.3

Abstract: We investigate the nature of the relation among stellar mass, star-formation rate, and gas-phase metallicity (the M * -SFR-Z relation) at high redshifts using a sample of 260 star-forming galaxies at z ∼ 2.3 from the MOSDEF survey. We present an analysis of the high-redshift M * -SFR-Z relation based on several emission-line ratios for the first time. We show that a M * -SFR-Z relation clearly exists at z ∼ 2.3. The strength of this relation is similar to predictions from cosmological hydrodynamical simulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
226
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(264 citation statements)
references
References 121 publications
36
226
2
Order By: Relevance
“…The predicted D16 indicator typically is ∼ 0.5 dex higher than the PP04 indicator at low masses, log(M * < 9.5. Additionally, we compared our measurements to the MOSDEF sample (Sanders et al 2018) and the previous measurements of the COSMOS protocluster and field Kacprzak et al (2015), which only used the PP04 indicator, and found similar results as our PP04 measurements ( Figure 2, top panels).…”
Section: Stacking Emission Linessupporting
confidence: 79%
See 2 more Smart Citations
“…The predicted D16 indicator typically is ∼ 0.5 dex higher than the PP04 indicator at low masses, log(M * < 9.5. Additionally, we compared our measurements to the MOSDEF sample (Sanders et al 2018) and the previous measurements of the COSMOS protocluster and field Kacprzak et al (2015), which only used the PP04 indicator, and found similar results as our PP04 measurements ( Figure 2, top panels).…”
Section: Stacking Emission Linessupporting
confidence: 79%
“…When at least one emission line shows significant sky interference, the point is unfilled. We compare to the MOSDEF metallicity measurements (Sanders et al 2018) at z ∼ 2.3, and to the ZFIRE measurements of the COSMOS proto-cluster and field in Kacprzak et al (2015). Small red arrows on the left side of each plot mark the location of solar metallicity.…”
Section: Stacking Emission Linesmentioning
confidence: 92%
See 1 more Smart Citation
“…If the [NII]/Hα ratio is substantially higher among our sample, the inferred η values could be overestimated. Indeed, [NII] emission from high-z galaxies appears higher than expected given their [OIII]/Hβ ratios (Steidel et al 2014;Masters et al 2014;Jones et al 2015;Shapley et al 2015, but see Sanders et al 2018). Increasing the [NII]/Hα ratio by 0.37 dex increases the predicted flux distribution, bringing models A and C in better agreement with observations.…”
Section: Contamination From [Nii]mentioning
confidence: 75%
“…Chisholm et al 2015). The MZR has been observed to hold also at redshifts out to 3 and beyond, nonetheless showing clear signs of evolution (Erb et al 2006a;Maiolino et al 2008;Mannucci et al 2009;Zahid et al 2011Zahid et al , 2014aYabe et al 2015;Ly et al 2016;Sanders et al 2018). In fact, high-z galaxies are observed to be less enriched than local ones for a given stellar mass, an effect that is more predominantly observed at low masses.…”
Section: Introductionmentioning
confidence: 95%